2019
DOI: 10.3390/nu11020286
|View full text |Cite
|
Sign up to set email alerts
|

Urine Caffeine Concentration in Doping Control Samples from 2004 to 2015

Abstract: The ergogenic effect of caffeine is well-established, but the extent of its consumption in sport is unknown at the present. The use of caffeine was considered “prohibited” until 2004, but this stimulant was moved from the List of Prohibited Substances to the Monitoring Program of the World Anti-Doping Agency to control its use by monitoring urinary caffeine concentration after competition. However, there is no updated information about the change in the use of caffeine as the result of its inclusion in the Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
87
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 45 publications
(56 reference statements)
0
87
0
10
Order By: Relevance
“…Of the analyzed athletes, the authors reported that rowers were among the highest users of caffeine. In a subsequent analysis from 2015, rowers were again found to have very high urine caffeine concentration after competition [5].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Of the analyzed athletes, the authors reported that rowers were among the highest users of caffeine. In a subsequent analysis from 2015, rowers were again found to have very high urine caffeine concentration after competition [5].…”
Section: Introductionmentioning
confidence: 93%
“…Given the widespread anecdotal use of caffeine in rowers [4,5], and the lack of scientific consensus on the effects of caffeine on rowing performance, this paper aims to conduct a systematic review and a meta-analysis of studies examining the effects of caffeine ingestion on rowing performance. Such an analysis would be of interest to the following: (a) athletes competing in rowing; (b) sports nutritionists; (c) coaches; and (d) researchers interested in further exploring the influence of caffeine supplementation on rowing performance.…”
Section: Introductionmentioning
confidence: 99%
“…The clear evidence provided by this special issue confirming the ergogenic effect of caffeine might be behind the slight increase in the use of caffeine in sports since its removal from the list of banned substances in 2004 [14]. By analyzing the concentration of caffeine in post-competition urine samples, it has been found that about three out of four athletes consume caffeine or caffeine-containing products to increase performance [14].…”
mentioning
confidence: 89%
“…Nowadays, caffeine is the most popular psychoactive substance in the world and data on urine caffeine concentration suggests that it is widely used by athletes before competition to enhance physical and mental fitness [1,2]. The research supporting the ergogenic effects of acute caffeine intake in a variety of sporting disciplines and exercise scenarios is extensive, and the International Olympic Committee has recently classified caffeine as a substance that enhances performance based on this strong scientific evidence [3].…”
Section: Abstract: Classification; Habituation; Caffeine Users; Dailymentioning
confidence: 99%